Crystal structure of 3-[(4-benzylpiperazin-1-yl)methyl]-5-(thiophen-2-yl)- 2,3-dihydro-1,3,4-oxadiazole-2-thione - Al-Omary, Fatmah A. M.; El-Emam, Ali A.; Ghabbour, Hazem A.; C. S., Chidan Kumar; Ching, Kheng Quah; Fun, Hoong Kun (International Union of Crystallography, 2015)
The title 1,3,4-oxadiazole-2-thione derivative, C18H20N4OS2, crystallized with two independent molecules (A and B) in the asymmetric unit. The 2-thienyl rings in both molecules are rotationally disordered over two orientations by approximately 180 about the single C—C bond that connects it to the oxadiazole thione ring; the ratios of site occupancies for the major and minor components were fixed in the structure refinement at 0.8:0.2 and 0.9:0.1 in molecules A and B, respectively. The 1,3,4-oxadiazole-2-thione ring forms dihedral angles of 7.71 (16), 10.0 (11) and 77.50 (12) (molecule A), and 6.5 (3), 6.0 (9) and 55.30 (12) (molecule B) with the major and minor parts of the disordered thiophene ring and the mean plane of the adjacent piperazine ring, respectively, resulting in approximately V-shaped conformations for the molecules. The piperazine ring in both molecules adopts a chair conformation. The terminal benzene ring is inclined towards the mean plane of the piperazine ring with N—C— C—C torsion angles of 58.2 (3) and 66.2 (3) in molecules A and B, respectively. In the crystal, no intermolecular hydrogen bonds are observed. The crystal packing features short S S contacts [3.4792 (9) A ° ] and – interactions [3.661 (3), 3.664 (11) and 3.5727 (10) A ° ], producing a threedimensional network.